1999
DOI: 10.1016/s0022-5223(99)70149-2
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation retrograde pneumoplegia in clinical lung transplantation

Abstract: Preimplantation retrograde flushing is not detrimental and helps to improve early graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 14 publications
1
38
0
2
Order By: Relevance
“…Retrograde flush has been described for lung and heart-lung preservation and has been found to achieve better clearance of red blood cells, better distribution of the flush solution along the tracheobronchial tree, and better preservation of the surfactant function [33][34][35][36]. Several centres currently perform a retrograde flush after the anterograde flush [37,38]. The retrograde flush can be performed in situ after the heart has been removed while the lungs are still ventilated, or later on the back table.…”
Section: Methods Of Lung Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrograde flush has been described for lung and heart-lung preservation and has been found to achieve better clearance of red blood cells, better distribution of the flush solution along the tracheobronchial tree, and better preservation of the surfactant function [33][34][35][36]. Several centres currently perform a retrograde flush after the anterograde flush [37,38]. The retrograde flush can be performed in situ after the heart has been removed while the lungs are still ventilated, or later on the back table.…”
Section: Methods Of Lung Preservationmentioning
confidence: 99%
“…The retrograde flush can be performed in situ after the heart has been removed while the lungs are still ventilated, or later on the back table. In a group of 14 patients, VENUTA et al [38] showed that the association of a retrograde flush to the anterograde flush can improve lung function after reperfusion of the transplanted lung.…”
Section: Methods Of Lung Preservationmentioning
confidence: 99%
“…Recently, the innovative approach of retrograde preservation of lung grafts has been shown to be very effective in the elimination of different kinds of thrombi from the pulmonary vasculature [6,[25][26][27][28]. Furthermore, the quality of organ preservation in terms of post-ischemic lung function was significantly improved following retrograde lung preservation [8,9,28,29,30].…”
Section: Commentmentioning
confidence: 99%
“…In addition, experimental work suggests that nitric oxide added to the flush solution or inhaled at the time of harvest provides a preservation advantage [45,46]. Combination of an antegrade and a retrograde [47,48] pulmonary vascular flush achieves more uniform distribution of flush solution and superior graft cooling. Lung hyperinflation is an excellent model of pulmonary oedema.…”
Section: Reperfusion Injurymentioning
confidence: 99%